The Integration of the Educational System in Indonesia Between the Islamic and National Identities - Musthofa, Tulus; Nur, Muhammad Sirojudin; Maghfuri, Amin (Proceeding International Conference on Religion, Science and Education, 2022)
Humanity knew education as the oldest form of politics before the politics of the tribe and the city. It is self-politics and selfmanagement. Perhaps the saying of Imam Al-Ghazali ((The most honorable of these policies after the prophethood is the benefit of knowledge and the refinement of the souls of people)). It represents the best expression of the value of learning and education and the honor of its mission and role. The educational process, in this sense, is the most important political process ever, which brings together all political action, in conception and practice. In this political educational context, we ask the following question: To what extent have contemporary Indonesian policies succeeded in building their educational systems, and to what extent did these policies achieve their strategic goals that they set since the birth of Indonesia after independence? Were these educational systems and educational policies national carrying out the projects of the Islamic nation, considering them the majority of the population and the reality, or were they projects that were projected on the reality of the nation to make it a new reality that wants to call itself the modernist embodying some dimensions of the development act in which the modern state of Indonesia has engaged in addition to other economic and political dimensions and developmental? There is no doubt that the people of Indonesia carry their own educational history before independence. There is no doubt that the spread Islamic schools carried a specific educational message expressing the structure, composition and aspirations of the community. There is also no doubt that these schools played their scientific and developmental role, and even carried the banner of popular resistance against colonialism in all its forms. These schools were a strong shield for the nation, defending its character and the nature of its Arab and Islamic identity. These national schools prevalent before and during colonialism are the ones that have been subjected to exclusion, criticism and abuse as traditional schools do not agree with the new development projects that believed in Western modernity and took it as the official ideology of the state and society. There are also other schools of a Western nature that have another role in building the educational system in Indonesia. And soon these emerging national states knew the beginning of the conflict between two types of schools, schools considered traditional and emerging schools considered modern, as society knew the beginning of the internal rift in its mental structure between a mentality considered traditional and backward and a new emerging mentality considered modern and modern. It is the modern school that wants torebuild society anew, not on the basis of its first rules and the history of its existing educational systems, but on the basis of new visions. So does Islamic identity conflict with nationalism, or do they complement and harmonize in the educational system in Indonesia? These questions the researcher tries to answer through this research.